The joint project on Vertisols management retrospect and prospects - Abebe, M.; Jutzi, S.C. (International Livestock Centre for Africa, 1993)
The Joint Vertisol Project which, by its nature and intention has dealt with natural resource research and development, has inherently addressed the complexity of factors and interactions among them. This has led to the two dimension strategy of choice or prioritisation: 1) issues related to research of the high-rainfall, low temperature and thus highly waterlogged Vertisols of the Ethiopian highlands, thereby providing a common denominator to collaborators for subsequent stages of research and development activities; and 2) high disciplinary priority to soil management related research; waterlogging and soil fertility being the most important constraints for Vertisols use high rainfall areas. Interinstitutional effort was therefore designed involving those in charge of training, research, development and extension. This would ensure more or less simulataneous design of both Vertisol - related management technologies and effective validation and transfer mechanisms commensurate with the constraints and opportunities of target farming systems. Seven years after its initiation, the Joint Vertisol Project has acquired a wealth of experiences which provide important lessons for future direction of its own programme and for similar activities elsewhere.